Bio-based materials: an alternative to synthetic polymers for the development of lab-on-a-chip devices - Zimmer, Morgane; Laurenceau, Emmanuelle; Trombotto, Stéphane; Jamois, Cécile; Deman, Anne-Laure (Frontiers in Lab on a Chip Technologies, 2026)
Lab-on-a-chip (LoC) devices have proved their potential for biomedical and analytical applications. Despite their growing demand, their environmental impacts remain insufficiently taken into account. These microfluidic devices are mainly made from petroleum-based materials like PDMS and thermoplastics, whose life-cycle (from resource extraction to disposal) poses ecological and health concerns. In response, a growing number of research papers are exploring bio-based alternatives, such as cellulose, PLA, chitosan, or zein. This review details properties of microfluidic devices made from these bio-based materials compared with more conventional materials, and particularly their impact on the environment from raw material sourcing through manufacturing to disposal. Although many of these materials are still in early stages of research, and published data is limited, developments are promising, and the associated technological challenges must be met. The alternative to plastics used for the manufacture of LoC could be a panel of complementary bio-based materials, locally sourced to support the local economy and limit transport, and which do not lead to new imbalances. This review advocates for a sustainable approach to material selection, encouraging the development of greener microfluidic devices.